Comparative analysis of the nutritional composition, digestibility, metabolomics profiles and growth influence of cow, goat and sheep milk powder diets in rat models - Yang, Chun; Pan, Jiancun; Pang, Shaojie; Hu, Shuang; Liu, Miao; Zhang, Xinyan; Song, Liping; Ren, Xiangnan; Wang, Zhongli (Frontiers in Nutrition, 2024)
Introduction The diversity of dairy products and the increasing consumption levels have led to a growing interest in goat and sheep milk, which are rich in essential nutrients and functional components. The study aims to explore the nutritional composition, growth performance, digestibility, and serum metabolic differences of milk powders from cow, goat, and sheep using LC–MS/MS-based metabolomics in rat models. Methods Sixty male Sprague-Dawley rats were fed with whole cow, goat, and sheep milk powder samples , and their feces and urine were analyzed for fat and protein content. LC/MS analysis was conducted using a Dionex UltiMate 3000 UHPLC system coupled with a Thermo Q EXACTIVE mass spectrometer, with data processed using Wekemo Bioincloud for quality control, normalization, comparisons with the KEGG database, statistical analyses, and selection of differential metabolites. Results The sheep milk powder showed highest protein and fat content level, while cow and goat milk powders separately demonstrated higher lactose and carbohydrate levels. Each milk powder had a unique mineral profile, with sheep milk powder containing the highest calcium content. All groups exhibited consistent growth in body weight and high rates of protein and fat digestibility. Metabolomics analysis revealed distinct metabolic profiles, with goat milk powder linked to steroid hormone biosynthesis and sheep milk powder associated with hormone regulation and bile acid pathways. Conclusion This study offers valuable insights into the metabolic implications of different milk powder sources, informing dietary choices and facilitating the development of targeted public health strategies to optimize nutritional intake and promote overall well-being.